High Pressure Falling Sinker Liquid Viscosity Determination without Supplementary Density Data: A New Approach - Minyu Zeng; Carl Schaschke (International Journal of Chemical Engineering)
Accurate measurement and determination of liquid viscosity data under high pressure conditions requires knowledge of liquid density data. In this study, a high pressure falling sinker-type viscometer was used to determine the viscosity of n-dodecane at elevated pressures up to 132 MPa without supplementary knowledge of liquid density. The viscometer, which involves the downward movement of a cylindrical sinker under the influence of gravity through the liquid contained within a closed tube, avoided the need for density data by repeating the sinker-timing experiments with two geometrically similar but different-sized sinkers thereby allowing the liquid density in the associated formulae to be eliminated. Furthermore, it was possible to subsequently derive liquid density. Both viscosity and density data were compared to published data for which good correlation was found for viscosity. To minimize errors, it is suggested that the two sinkers for such an approach should be of sufficiently differing densities.